Giant maxillary ameloblastic fibroma, a case report from university hospital of yalgado ouédraogo (Burkina Faso) - Idani Motandi; Millogo Mathieu; Badini Soutongnoma Ahmed Patrick; Ili Bévianda Vincent; Zango Adama; Konsem Tarcissus (Elsevier, 2021)
Ameloblastic fibroma (AF) is a rare mixed odontogenic benign tumor with mesenchymal and epithelial components. It occurs mostly in young subjects with a male predominance (average age 15 years) and a predominant mandibular location. It is diagnosed histologically and treated surgically. The postoperative evolution is favorable in general with possible recurrence or even malignant transformation. We report here a case of a large atypical location in a young patient. The management of giant forms and the possibility of malignant transformation are the main difficulties in the management of this pathology in our under medicalized environment.